Mapping precursors researchers of the area of drug prevention in educational contexts in Brazil - Julia Ferreira Bernardo; Bruno de Oliveira Pinheiro; Jesús Pascual Mena-Chalco; Denise de Micheli (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2018)
Even with the growing interest of researchers in the implementation and execution of drug prevention projects in educational contexts, little is known about the effectiveness of the actions and projects developed, as well as the researchers that develop this theme. This article aimed to group information at the national level of precursors researchers the area of studies and knowledge about drug prevention in educational contexts and to present a method for the systematic mapping that identify these researchers. Using the scientometric analysis in the Bank of Thesis and Dissertations of CAPES and in the Lattes Platform, using the ScriptLattes software, the bibliographic productions, orientations, collaboration network and geolocation map of a group of 61 Brazilian researchers were identified. It is concluded that strategies for the identification of researchers and their scientific production help in the integration and sharing of information, increase the exchange of knowledge and experiences, and evidence a national mapping of researchers in certain areas.